Have our du’aas turned into sheer civil expressions? - Hasan, Md. Mahmudul (2022)
If expressions of du’aa do not come from the heart and if people only say them as civil utterances or type them on the screen as niceties, they may not be efficacious from a religious point of view. Therefore, supplications for oneself and for others should be profound acts of submission and obedience to God, and only then it can be hoped that they will be answered. Turning them into “polite meaningless words” may not be sanctioned by a religion like Islam.